PENGARUH FAKTOR INTERNAL DAN EKSTERNAL PERUSAHAAN TERHADAP TIMELINESS LAPORAN KEUANGAN - Luanda Satya Pratama (Diponegoro Journal of Accounting, 2014)
Timeliness refersto the need for accounting information to be presented to the users in time to fulfill their decision making needs.Timeliness of accounting information is highly desirable since information that is presented timely is generally more relevant to users while conversely, delay in provision of information tends to render it less relevant to the decision making needs of the users. Timeliness principle is therefore closely related to the signalling theory.The sample of this research are manufacturing companies listed on the Indonesian Stock Exchange (BEI) in the year 2009 to 2011. Data collection methods used in this research is using purposive sampling method and obtained a total sampe of 225 companies. The research data and hypothesis were analyzed using logistic regression analysis. The results of this research showed that the factors which have a significant influence for Timeliness are profitability, solvability, and the public accountant’s size. While the other factors, the existence of internal auditor division and the firm’s size are not proven having a significant influence for Timeliness.